Personality traits across the life cycle: Disentangling age, period, and cohort effects - Bernd Fitzenberger; Gary Mena; Jan Sebastian Nimczik; Uwe Sunde (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
Economists increasingly recognise the importance of personality traits for socioeconomic outcomes, but little is known about the stability of these traits over the life cycle. Existing empirical contributions typically focus on age patterns and disregard cohort and period influences. This paper contributes novel evidence for the separability of age, period, and cohort effects for a broad range of personality traits based on systematic specification tests for disentangling age, period and cohort influences. Our estimates document that for different cohorts, the evolution of personality traits across the life cycle follows a stable, though non-constant, age profile, while there are sizeable differences across time periods.
Keywords: D8; J1; 330; Big Five Personality Traits; Locus of Control; Risk Attitudes; Age-Period Cohort Decomposition; Life Cycle